HISTORICAL EARTHQUAKES IN THE REGION OF LEFKADA ISLAND , IONIAN SEA - ESTIMATION OF MAGNITUDES FROM EPICENTRAL INTENSITIES - Fokaefs, A.; Papadopoulos, G. A. (Bulletin of the Geological Society of Greece, 2004)
Historical documentation of strong shocks for Lefkada Island, Ionian Sea, exists since the 16th century A.D. In this paper we establish a relation between magnitude and maximum intensity from twenty-nine instrumental events that hit the area in the past. Then, on the basis of historical documentary sources we reevaluate the intensities of strong historical earthquakes, their maximum intensity being observed on Lefkada in the time interval from AD1577 to 1911, recalculate their magnitudes on the basis of the magnitude/intensity relation and, finally, compile a new catalogue of historical earthquakes. The results obtained are of importance for the seismicity studies and seismic hazard assessment in the area.